1999
DOI: 10.1109/55.784447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitridation pressure on the characteristics of gate dielectrics annealed in N2O ambient

Abstract: Effects of N 2 O pressure during oxynitridation on the characteristics of ultrathin gate dielectrics have been investigated. Reoxidation in N 2 O ambient showed three distinguished oxidation regions as a function of tube pressure; that is, enhancement at 10-40 torr, retardation at 40-100 torr, and enhancement at 100-600 torr. The N2O-nitridation at 40 torr incorporated much less nitrogen in oxide bulk than that at near-atmospheric pressure. The 40 torr N2O-nitridation case exhibited about 70% of nitrogen incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Regarding the impact of nitridation on TDDB/HBD, to the best of our knowledge, there are a very limited number of publications addressing this subject. Among them, are the papers by Joo et al [ 25 ] and Mazumder et al [ 26 ], which analyzed how nitridation in NO ambient impacts TDDB and concluded that low-pressure nitridation results in the improvement of TDDB robustness, while nitridation at an increased pressure leads to poorer TDDB characteristics. A TDDB lifetime improvement due to annealing in the NO ambience was reported by Chen et al [ 27 ], while Lee et al [ 28 ] demonstrated that ex situ N annealing has a very weak impact on TDDB.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the impact of nitridation on TDDB/HBD, to the best of our knowledge, there are a very limited number of publications addressing this subject. Among them, are the papers by Joo et al [ 25 ] and Mazumder et al [ 26 ], which analyzed how nitridation in NO ambient impacts TDDB and concluded that low-pressure nitridation results in the improvement of TDDB robustness, while nitridation at an increased pressure leads to poorer TDDB characteristics. A TDDB lifetime improvement due to annealing in the NO ambience was reported by Chen et al [ 27 ], while Lee et al [ 28 ] demonstrated that ex situ N annealing has a very weak impact on TDDB.…”
Section: Introductionmentioning
confidence: 99%